Effects of Different Supplemental Levels of Eucommia ulmoides Leaf Extract in the Diet on Carcass Traits and Lipid Metabolism in Growing–Finishing Pigs - Yang, Yuhuan; Li, Fengna; Guo, Qiuping; Wang, Wenlong; Zhang, Lingyu; Yin, Yunju; Gong, Saiming; Han, Mengmeng; Yin, Yulong (Frontiers in Veterinary Science, 2022)
This study examined the effects of dietary Eucommia ulmoides leaf extract (ELE) supplements on carcass traits and lipid metabolism in finishing pigs. A total of 144 crossbred (Duroc × Landrace × Yorkshire) piglets with an average initial weight of 10.11 ± 0.03 kg was randomly allotted to four treatment groups, each with six replicates and six piglets per replicate. Each group of pigs was fed a basal diet or a diet supplemented with increasing levels of ELE (0.1, 0.2, or 0.3%). The results showed that adding ELE had no negative effect on the growth performance of pigs. Dietary supplements of 0.1% ELE significantly increased carcass weight (P < 0.01 ), dressing percentage (P < 0.01), carcass length (P < 0.05), and eye muscle area (P < 0.05). Compared with the control group, a 0.2% ELE supplement significantly increased (P < 0.01) the levels of adiponectin, insulin-like growth factor 1, and hormone-sensitive lipase and lipoprotein lipase activity in the serum. Histological examination showed that ELE inhibited fat deposition in the backfat tissue. Lipid metabolism-related biochemical indices and mRNA expression levels were improved after supplementing diets with ELE. Moreover, all three levels of ELE dramatically upregulated (P < 0.05) the protein levels of p-AMPK-α and p-ACC. In summary, adding ELE to pig diets could improve the carcass traits of finishing pigs, and exert a lipid-lowering effect by activating the AMPK-ACC pathway and regulating mRNA expression levels related to lipid metabolism. Supplementing the diet with 0.1-0.2% ELE is the optimal range to reduce fat deposition in pig backfat tissue.